Experience of finding footwear and factors contributing to footwear choice in people with gout: a mixed methods study using a web-based survey - Brenton-Rule, Angela (J Foot Ankle Res, 2019)
BACKGROUND: Gout frequently affects the foot, particularly the first metatarsophalangeal joint. People with gout commonly wear ill-fitting footwear that lacks cushioning and support, which may further contribute to foot pain and disability. Footwear with good cushioning and motion control may be an effective non-pharmacological intervention. Currently, there is limited understanding about the footwear experience in people with gout. The aim was to understand footwear characteristics, experience of finding footwear, and factors contributing to footwear choice, in people with gout. METHODS: A web-based survey of people visiting a gout education website. Participants self-reported a diagnosis of gout. The 17-item survey included questions to elicit demographic and clinical characteristics, type of footwear worn, level of difficulty finding appropriate footwear, and factors contributing to choices about footwear. A mixed quantitative and qualitative methodology was used to report survey findings. RESULTS: Survey respondents (n = 83) were predominately White/Caucasian (84%), male (58%), and aged between 46 and 75 years-old (73%). Thirty-nine percent were newly diagnosed (< 12 months), 43% had gout for 1–10 years, and 19% had disease over 10 years. Gout flares in the feet were reported by 77 (93%) respondents, mostly in the big toe joint (73%). Seventy-six (92%) participants completed questions about footwear. Closed-in athletic shoes (88%), sturdy walking shoes (79%), and casual closed-in slip-on shoes (63%) were most frequently worn. Orthopaedic shoes were worn least often (16%). Comfort, fit, support, and ease to put on/take off were the features most often rated as important or very important when choosing footwear. Over half the respondents (64%) reported difficulty in finding footwear. Three categories, encompassing seven subcategories, were identified from the qualitative analysis to describe experiences of footwear. Categories included difficulty finding suitable shoes; impact of shoes on activity; and preferred footwear. CONCLUSIONS: People with gout need comfortable shoes that conform to the foot, have a wide opening, made from pliable materials with adjustable straps. The main barriers related to footwear include difficulty finding shoes that are wide enough, suitable for work and aesthetically pleasing. These findings provide clinicians with important insights into the priorities and needs of people with gout that should be considered when developing footwear interventions.